Surviving the new millennium lessons from the Asian crisis - Ang, Swee Hoon (McGraw-Hill, 2000)
This book focuses on three main themes. First, it provides a macro perspective of the root causes of the Asian crisis. Second, it discusses the actions businesses have to take to prepare for the new millennium. And third, it identifies the indicators of the success of such efforts and the warning signs of the arrival of a new crisis." "As businesses weather the economic storm, they need to adapt to the changing financial, marketing, human resources, and competitive landscapes. This book provides strategic implications in these key areas and provides numerous examples of how businesses adapted to the crisis and are preparing for the new millennium." "Set in the context of the Asian crisis, this book is applicable broadly as the strategies and underlying principles are relevant and valuable in many contexts. The Asian crisis has provided an interesting and instructive context to study what businesses have to do to succeed in the new millennium.